Aëtiana : the method and intellectual context of a doxographer. Vol. 1, Sources - Mansfeld, Jaap. (Philosophia Antiqua, 1997)
In 1879 the young German scholar Hermann Diels published his celebrated Doxographi Graeci , (in which the major doxographical works of antiquity are collected and analysed). Diels' results have been foundational for the study of ancient philosophy ever since. In their ground-breaking study the authors focus on the doxographer Aëtius, whose work Diels reconstructed from various later sources. First they examine the antecedents of Diels' Aëtian hypothesis. Then Diels' theory and especially the philological techniques used in its formulation are subjected to detailed analysis. The remainder of the volume offers a fresh examination of the sources for our knowledge for Aëtius. Diels' theory is revised and improved at significant points. Subsequent volumes will examine the contents and methods of the doxographer and his antecedents in earlier Greek philosophy. No scholar concerned with the history of ancient philosophy can afford to ignore this study.